About hematopoietic properties of peripheral blood lymphocytes RNA from patients with polycythemia vera and healthy donors - A. G. Babaeva; N. M. Gevorkyan; N. V. Tishevskaya; L. L. Golovkina; Yu. O. Muratova; A. A. Ragimov (Онкогематология, 2015)
Total RNA isolated from peripheral blood lymphocytes of donor and patient with polycythemia, stimulates hematopoiesis in rats with toxic  aplastic anemia due to benzene administration. Total RNA of lymphocytes from polycythemia patient has a more pronounced effect on the erythroid, myeloid and megakaryocytic hematopoiesis comparing to total RNA from donor lymphocytes. The greatest stimulatory effect of RNA observed after 21 days from the start of experiment. Total RNA of lymphocytes from polycythemia patient largely activates erythropoiesis promoting restoration of reticulocyte count in animals with aplastic anemia.